Radio SETI observations of the interstellar object ′OUMUAMUA. (February 2019) - Harp, G.R.; Richards, Jon; Jenniskens, Peter; Shostak, Seth; Tarter, Jill C.
Abstract: Motivated by the hypothesis that 'Oumuamua could conceivably be an interstellar probe, we used the Allen Telescope Array to search for radio transmissions that would indicate a non-natural origin for this object. Observations were made at radio frequencies between 1 and 10 GHz using the Array's correlator receiver with a channel bandwidth of 100 kHz. In frequency regions not corrupted by man-made interference, we find no signal flux with frequency-dependent lower limits of 0.01 Jy at 1 GHz and 0.1 Jy at 7 GHz. For a putative isotropic transmitter on the object, these limits correspond to transmitter powers of 30 mW and 300 mW, respectively. In frequency ranges that are heavily utilized for satellite communications, our sensitivity to weak signals is badly impinged, but we can still place an upper limit of 10 W for a transmitter on the asteroid. For comparison and validation should a transmitter be discovered, contemporaneous measurements were made on the solar system asteroids 2017 UZ and 2017 WC with comparable sensitivities. Because they are closer to Earth, we place upper limits on transmitter power to be 0.1 and 0.001 times the limits for 'Oumuamua, respectively. Highlights: We report new cm wave radio observations of the interstellar object, 'Oumuamua. Results are compared with contemporaneous observations of two in-solar system asteroids. Observations covered frequencies 1–10 GHz with 100 kHz resolution. The spectral shape of all asteroids was essentially the same. We see no evidence of artificial transmitters (isotropic power < 0.01–10 W).